β-PdBi2 monolayer: two-dimensional topological metal with superior catalytic activity for carbon dioxide electroreduction to formic acid - Zhu, X.; Wang, Yu; Jing, Y.; Heine, Thomas; Li, Yafei (Materials Today Advances, 2020)
The lack of efficient electrocatalysts has been a main obstacle for the large-scale commercialization of CO2 electroreduction. In this work, we demonstrate that two-dimensional (2D) β-PdBi2 monolayer is a promising solution for this issue. β-PdBi2 monolayer is a stable 2D crystal, and the three-dimensional bulk interlayer energy is similar as for other layered materials that can be exfoliated into 2D crystals. Interestingly, β-PdBi2 monolayer has rather intriguing electronic properties: while being metallic, it also has a non-trivial topological point. Remarkably, the extra electronic states at the Fermi level induced by the intrinsic spin-orbit coupling effect significantly enhance the adsorption of OCHO∗ intermediate on β-PdBi2 monolayer, resulting in a rather small onset potential of −0.26 V vs. RHE for CO2 electroreduction to HCOOH. These results not only suggest a promising candidate for CO2 electrolysis but also deepen our understanding of the factors dominating the catalytic activity of 2D materials.
CRIS-Team Scopus Importer:2022-04-14
Keywords: CO; Density functional theory calculations; Formic acid production; Spin-orbit coupling